2000
DOI: 10.1037/0278-6133.19.3.223
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of cigarette smoking from adolescence to adulthood in a midwestern community sample: Multiple trajectories and their psychosocial correlates.

Abstract: Previous research on the natural history of smoking has focused on overall group trajectories without considering the possibility of risk subgroup variation. To address this limitation, the authors of the present study aimed to identify subgroups with varying trajectories of smoking behavior. The authors accomplished this within a cohort-sequential study of a large community sample (N = 8,556) with measurements spanning ages 11-31. After removing 2 a priori groups (abstainers and erratics), the authors empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
429
3
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(476 citation statements)
references
References 32 publications
37
429
3
4
Order By: Relevance
“…There is considerable evidence in the literature that the smoking behaviour of friends has a major influence on the current and future smoking of adolescents and young adults (Flay et al, 1994(Flay et al, , 1998Distefan et al, 1998;Engels et al, 1999;Chassin et al, 2000;Leatherdale et al, 2005). If, as our study found, MZ pairs are more similar in their friends' smoking behaviours than are DZ pairs, this could explain some or all of the greater correlation of smoking observed in MZ twins.…”
Section: Discussionsupporting
confidence: 55%
“…There is considerable evidence in the literature that the smoking behaviour of friends has a major influence on the current and future smoking of adolescents and young adults (Flay et al, 1994(Flay et al, , 1998Distefan et al, 1998;Engels et al, 1999;Chassin et al, 2000;Leatherdale et al, 2005). If, as our study found, MZ pairs are more similar in their friends' smoking behaviours than are DZ pairs, this could explain some or all of the greater correlation of smoking observed in MZ twins.…”
Section: Discussionsupporting
confidence: 55%
“…Also, as seen in 1 The trajectories reported in Chassin et al (2000) examined earlier ages and produced similar but not identical solutions (see Chassin et al, in press, for details). Chassin et al (2000) labeled groups as abstainers, experimenters, early stable (now called early-onset persistent), late stable (now called late onset), erratics (now called relapsers/remitters), and quitters (now called developmentally limited smokers to differentiate them from the successful quitters who quit in adulthood and were not identified in the earlier analysis) The current solution also differentiated stable quitters as an a priori group and identified a high school-onset group. 2 We also estimated models defining parents' current smoking as at least daily and eliminating nondaily smokers, as well as reclassifying nondaily smokers as nonsmokers.…”
Section: Bivariate Associations With Parent Smoking Trajectorymentioning
confidence: 75%
“…These trajectories represent developmental phenotypes of smoking, and, similar to the antisocial behavior literature, they may also vary in the risk that they carry for the intergenerational transmission of smoking. Chassin et al (2000) found that a trajectory group that was of particular interest for intergenerational transmission was the group of early-onset persistent smokers. Compared with other smoking trajectories, these individuals began smoking at a young age, escalated steeply to a high rate of smoking, and persisted in their smoking into adulthood, and they had the highest levels of smoking among their biological parents.…”
mentioning
confidence: 99%
“…First, the analytical sample (N = 847) included a large number of adolescents recruited in secondary schools. Given that adolescence is the developmental stage when individuals are most likely to experiment with tobacco (Chassin et al, 2000), this period was optimal for evaluating risk factors for ND. Second, the measurement definitions of ND and never-smoking status were rigorous.…”
Section: Strengthsmentioning
confidence: 99%